Model Pengembangan Kewirausahaan Melalui Pembiayaan Wakaf Uang di Lembaga Wakaf Muhammadiyah Kabupaten Cilacap - Een Juhanah; Nurul Hilmiyyah; Dede Abdul Fatah (Islamic Economics Department, Faculty of Islamic Economics and Business, UIN SULTHAN THAHA SAIFUDDIN JAMBI, 2022)
Purpose – This study is to identify the obstacles in conducting an entrepreneurial development model with cash waqf financing in Cilacap Regency and formulate an entrepreneurship development model with cash waqf financing through business charities at the Muhammadiyah Waqf Institution, Cilacap Regency Design/methodology/approach - This study is a qualitative descriptive study to analyze the model of entrepreneurship waqf development in Cilacap Regency using the triangulation method at the time of data collection and analysis which is expected to confirm validity of the data or information obtained in various different perspectives. The population in this study is the waqf manager at the Muhammadiyah institution (Muhammadiyah Regional Leader) Cilacap Regency, Central Java. While the sample used is purposive sampling by selecting the Muhammadiyah Branch Manager (PCM) who is the most advanced in managing business/entrepreneurial charities, namely PCM Majenang Finding - Based on the results of processing secondary data and primary data, the obstacles commonly encountered by the selected Muhammadiyah Business Amal (AUM) are financial problems.